2014
DOI: 10.1039/c3ra41173g
|View full text |Cite
|
Sign up to set email alerts
|

Semi-transparent Si-rich SixC1−x p–i–n photovoltaic solar cell grown by hydrogen-free PECVD

Abstract: A semi-transparent silicon-rich (Si-rich) silicon carbide (Si x C 1Àx ) based thin-film p-i-n junction photovoltaic solar cell is demonstrated, which is synthesized by hydrogen-free plasma enhanced chemical vapor deposition (PECVD) with the conversion efficiency optimized by detuning plasma power and intrinsic layer thickness. The hydrogen-free PECVD process effectively decelerates the decomposition of hydrogen from the Si-rich Si x C 1Àx films so as to facilitate the passivation of surface dangling bonds. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…8 Cheng et al optimized the i-Si x C 1Àx thickness to 25 nm in Si-rich Si x C 1Àx -based solar cells for enhancing the filling factor and conversion efficiency to 0.25 and 1.7%, respectively. 9 Estrada et al 10 demonstrated Si x C 1Àx based thin-film transistors with a field-effect mobility of up to 1.9 Â 10 À2 cm 2 V À1 s À1 . Furthermore, Si x C 1Àx has been employed in high-temperature and highpower electronics for maintaining device sensitivity and stability under extreme environments because of its superior thermal stability and chemical inertness.…”
Section: Introductionmentioning
confidence: 99%
“…8 Cheng et al optimized the i-Si x C 1Àx thickness to 25 nm in Si-rich Si x C 1Àx -based solar cells for enhancing the filling factor and conversion efficiency to 0.25 and 1.7%, respectively. 9 Estrada et al 10 demonstrated Si x C 1Àx based thin-film transistors with a field-effect mobility of up to 1.9 Â 10 À2 cm 2 V À1 s À1 . Furthermore, Si x C 1Àx has been employed in high-temperature and highpower electronics for maintaining device sensitivity and stability under extreme environments because of its superior thermal stability and chemical inertness.…”
Section: Introductionmentioning
confidence: 99%
“…From this point of view, the nonstoichiometric silicon carbide (SiC) is recently considered as one of the potential candidates. The nonstoichiometric SiC has been extensively investigated for different applications such as light-emitting diodes (LEDs), solar cells, and detectors. Benefiting from the relatively wide bandgap energy ( E g , for the commonly encountered polymorph of a-SiC E g = 3.05 eV) and high thermal stability, the nonstoichiometric SiC offers a low absorption coefficient and a high optical damage threshold, which is suitable for high-power operation. Moreover, the nonstoichiometric SiC is predicted to exhibit high nonlinear refractive index at optical telecommunication wavelengths; however, there is lack of literature discussing the transient variation on the nonlinear refractive index of nonstoichiometric SiC at near-infrared wavelengths …”
mentioning
confidence: 99%
“…Recently, a group of scientists developed a semitransparent non-stoichiometric photovoltaic solar cell based on Si-rich Si x C 1-x p-i-n grown by hydrogen-free PECVD at low plasma power (Cheng et al, 2014). During the fabrication process using RF plasma power ranging from 20-100 W (40W step) at a power density of 560 mW cm −2 , the optical bandgap of Sirich Si x C 1-x absorbing layer was effectively controlled by varying the Si/C ratio.…”
Section: Silicon Solar Cellsmentioning
confidence: 99%
“…Furthermore, the charge collection process was realized using ITO and Al electrode which were connected to P-type SiC and N-type SiC films respectively (see Figure 7). Ultimately, the optimized device fabricated with an absorbing layer of 25 nm exhibited the highest power conversion efficiency (Cheng et al, 2014). The optimization of deposition parameters remains a key challenge for better performance of the devices (see table 2).…”
Section: Silicon Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation